Acoustic biomass and distribution of Jack mackerel Trachurus murphyi in Peru - Segura, Marceliano (2013)
This paper analyzes the results of acoustic stock assessment surveys for Jack mackerel Trachurus murphyNichols 1920 conducted in Peruvian waters between 1983 and 2012. Since 1983 Jack mackerel T. murphyiwas included as a target species to be assessed during the pelagic stock assessment surveys executed by the Peruvian Institute of Marine Research. Due to the emphasis on the assessment of anchovy Engraulis ringens and sardine Sardinops sagaxwhen this species was abundant, these surveys usually took place during the austral summer and only covered the first 100 nautical miles from the coast, and only occasional surveys were conducted in other seasons or surveyed as far as 200 nm offshore. A maximum biomass of 8.51 million t of T. murphyiin Peruvian waters estimated through acoustics during a survey carried out in autumn (March-May) 1983. In the following years acoustic biomass estimates ranged between 180 thousand t in 1985 and another maximum of 8.47 million t in 1993, to then decreased gradually to a minimum of 1239 t in 2010, with a slight recovery in 2011 and 2012. The areas of distribution of T. murphyihave been fluctuating markedly throughout the observed period.